Barium titanate-silver niobate relaxor ferroelectric ceramic with high energy storage characteristic as well as preparation method and application of barium titanate-silver niobate relaxor ferroelectric ceramic

By introducing silver niobate into barium titanate, new A-O coupling is constructed, relaxation behavior is induced, and the breakdown field strength and energy storage density of ceramics are improved, and the insufficient energy density of ceramic capacitors and the environmental hazards of lead-based ceramics are solved. Problem, a high performance lead-free ceramic material is provided for pulse capacitors.

CN119161182AActive Publication Date: 2024-12-20SHANGHAI INST OF CERAMIC CHEM & TECH CHINESE ACAD OF SCI
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411196543.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-29
Publication Date
2024-12-20
Estimated Expiration
2044-08-29

AI Technical Summary

Technical Problem

The low energy density of existing ceramic capacitors and the harm of lead-based ceramics to the environment and the human body limit their application, and the energy storage density of lead-free dielectric materials is not sufficient to meet the needs of integrated, lightweight and miniaturization of pulse power systems.

Method used

Develop a high-energy storage characteristic barium titanate-silver niobate relaxation ferroelectric ceramic. By introducing silver niobate into barium titanate, new A-O coupling is constructed, which induces relaxation behavior, improves breakdown field strength and energy storage. Density and a simple and reliable preparation method is adopted.

Benefits of technology

Achieve high breakdown field strength (554~665kV/cm) and high energy storage density (4.02~6.04J/cm3), while maintaining high efficiency (81.9~86.8%), providing high performance alternative storage for pulse capacitors Energy material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119161182A_ABST
    Figure CN119161182A_ABST
Patent Text Reader

Abstract

The invention relates to a barium titanate-silver niobate relaxor ferroelectric ceramic with a high energy storage characteristic, and a preparation method and application of the barium titanate-silver niobate relaxor ferroelectric ceramic. The chemical composition of the barium titanate-silver niobate relaxor ferroelectric ceramic with the high energy storage characteristic is (1-x) BaTiO3-xAgNbO3, wherein x is larger than or equal to 0.06 and smaller than or equal to 0.08.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of functional ceramics, and in particular relates to a barium titanate-silver niobate relaxor ferroelectric ceramic with high energy storage characteristics, and a preparation method and application thereof. Background Art

[0002] In recent years, with the rapid development of electric vehicles, aerospace industry and portable electronic products, the demand for integrated, compact and efficient electronic systems has increased dramatically. Ceramic capacitors, as key components of pulse power systems, can simultaneously provide high power density, fast charge and discharge speed, high breakdown strength and high stability over a wide temperature range. However, compared with electrochemical energy storage devices, the low energy density of ceramic capacitors limits their application. Lead-based ceramics are still the mainstream of current commercial pulse capacitors. Due to the serious harm to the environment and human body in the links of raw material mining, device preparation and recycling, their use has been restricted by various countries. The low energy storage density of lead-free dielectric materials currently poses a huge challenge to the integration, lightweight and miniaturization of pulse power systems. Therefore, it is urgent to develop lead-free ceramic materials with high energy storage density.

[0003] BaTiO3 is currently the most widely used dielectric material due to its high dielectric constant, low production cost and stable chemical structure. However, the long-range ordered dipole arrangement in the unmodified BaTiO3 ceramic material will lead to high remnant polarization, and the lack of A-site polarization will lead to low saturation polarization, which greatly hinders the enhancement of energy storage performance. Relaxation design can reduce the remnant polarization of ferroelectric materials and increase the breakdown field strength, so it is considered to be an effective measure to improve the energy storage performance of ferroelectric materials.

[0004] At present, there have been a lot of reports on improving the energy storage properties of barium titanate-based ceramic materials. 0.8 Bi 0.2 )(Ti 0.58 Zr 0.14 Sc 0.18 Mg 0.04 Nb 0.05 Ta 0.01 )O3 ceramics achieve 5.18 J / cm through high entropy at the B site 3 Recyclable energy density (reference: J.Alloy.Compd.2024,970,8.); 0.85(0.9BaTiO3-0.1Bi(Mg 2 / 3 Ta 1 / 3 )O3-0.15NaTaO3 ceramics can achieve 6.02J / cm 3Energy storage density (reference: J. Eur. Ceram. Soc. 2024, 44, 3916.). However, the saturation polarization intensity of the modified barium titanate-based ceramics in the above study was greatly reduced (18 μC / cm at an electric field of 640 kV / cm and 18 μC / cm at an electric field of 640 kV / cm respectively). 2 , 27μC / cm under 718kV / cm electric field 2 ) also limits the improvement of energy storage properties of barium titanate-based ceramics. Summary of the invention

[0005] In view of the above technical problems, the purpose of the present invention is to provide a high polarization and high energy storage characteristic barium titanate-silver niobate relaxor ferroelectric ceramic and its preparation method and application. The ceramic material provided by the present invention has excellent performance, lead-free and environmentally friendly, simple preparation, and has the characteristics of high breakdown field strength, high energy storage density and efficiency, providing a high-performance alternative energy storage material for devices such as pulse capacitors.

[0006] In a first aspect, the present invention provides a barium titanate-silver niobate relaxor ferroelectric ceramic with high energy storage characteristics, wherein the chemical composition of the barium titanate-silver niobate relaxor ferroelectric ceramic is: (1-x)BaTiO3-xAgNbO3; wherein 0.06≤x≤0.08.

[0007] Preferably, the breakdown field strength of the high energy storage characteristic barium titanate-silver niobate relaxor ferroelectric ceramic is 554-665 kV / cm, and the recoverable energy density is 4.02-6.04 J / cm 3 , the energy storage efficiency is 81.9~86.8%.

[0008] In a second aspect, the present invention provides a method for preparing the above-mentioned barium titanate-silver niobate relaxor ferroelectric ceramic with high energy storage characteristics, the preparation method comprising the following steps: (1) weighing barium carbonate powder, titanium dioxide powder, silver oxide powder, and niobium pentoxide powder as raw materials according to the element stoichiometric ratio in the chemical formula (1-x) BaTiO3-xAgNbO3, mixing the raw materials, calcining the raw materials under an oxygen atmosphere, and then finely grinding and sieving the raw materials to obtain ceramic powder; (2) adding a binder to the ceramic powder, granulating, screening and molding to obtain a ceramic green body; (3) Arranging and sintering the ceramic green body in an oxygen atmosphere to obtain the barium titanate-silver niobate relaxor ferroelectric ceramic with high energy storage characteristics.

[0009] Preferably, in step (1), the purity of the raw material powder is at least 99%; The mixing method is planetary ball milling, and the mixing parameters include: the ball milling medium is anhydrous ethanol, the grinding balls are zirconia balls and zirconia columns, the ball milling speed is 200-240r / min, and the ball milling time is 4-6h; preferably, the particle size of the zirconia balls is 6mm, the size of the zirconia columns is 10mm in diameter×10mm in height, the mass of the zirconia balls and zirconia columns in the grinding balls each accounts for half, and the ball milling time is 4h.

[0010] Preferably, in step (1), the calcination temperature is 1270-1330°C, and the calcination time is 2-3h, preferably 3h; The mesh number of the fine grinding and sieving is 40 meshes.

[0011] Preferably, in step (2), the binder is a polyvinyl alcohol aqueous solution with a concentration of 6 to 7 wt.%, and the added amount is 6 to 7 wt.% of the mass of the ceramic powder; and the mesh size of the granulation screening is 40 meshes.

[0012] Preferably, in step (3), the process of plastic removal is: heating to 600-800°C at a rate of 2-4°C / min and keeping warm for 2-3h; preferably, heating to 800°C at a rate of 2°C / min and keeping warm for 2h.

[0013] Preferably, in step (3), the sintering process is: heating to 1000°C at a heating rate of 2-4°C / min, then heating to 1220-1280°C at a heating rate of 2°C / min, and keeping the temperature for 2-3h.

[0014] In a third aspect, the present invention provides an energy storage ceramic element, which includes: the above-mentioned barium titanate-silver niobate relaxor ferroelectric ceramic with high energy storage characteristics, and electrodes distributed on the surface of the barium titanate-silver niobate relaxor ferroelectric ceramic with high energy storage characteristics.

[0015] In a fourth aspect, the present invention provides an application of the above-mentioned barium titanate-silver niobate relaxor ferroelectric ceramic with high energy storage characteristics in multilayer ceramic capacitors and pulse power devices.

[0016] Beneficial Effects Silver niobate has high polarization strength due to its short covalent Ag-O bond. The present invention dissolves silver niobate, an antiferroelectric material with high spontaneous polarization strength, into barium titanate. On the basis of induced relaxation, the introduction of silver niobate constructs a new AO coupling in the barium titanate ceramic, thereby compensating for the polarization loss in the relaxation process of the barium titanate ceramic. The relaxed barium titanate-silver niobate relaxor ferroelectric ceramic exhibits a high polarization response under an applied electric field, and the breakdown field strength of the ceramic is significantly improved (554-665 kV / cm). Finally, the energy storage performance of the ceramic is significantly improved, and the recoverable energy density of the ceramic is 4.02-6.04 J / cm 3, energy efficiency is 81.9-86.8%; The preparation process of the invention is simple, reliable, and environmentally friendly, and shows great application potential in the fields of high-power pulse capacitors and the like. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 X-ray diffraction images of barium titanate-silver niobate ceramic materials prepared in Examples 1 and 2 and Comparative Examples 1-3; Figure 2 , 3 Surface morphology of the high energy storage characteristic barium titanate-silver niobate relaxor ferroelectric ceramics prepared in Examples 1 and 2; Figure 4 , 5 The unipolar hysteresis loop diagram of the high energy storage characteristic barium titanate-silver niobate relaxor ferroelectric ceramic prepared in Examples 1 and 2; Figure 6 , 7 8 is a unipolar hysteresis loop diagram of the barium titanate-silver niobate ferroelectric ceramic prepared in Comparative Examples 1-3; Fig. 9 This is a performance comparison diagram of barium titanate-silver niobate ceramics with different components prepared in Examples 1 and 2 and Comparative Examples 1-3; Fig.10 The dielectric thermograms of barium titanate-silver niobate ceramics with different components prepared in Examples 1 and 2 and Comparative Examples 1-3 at a frequency of 1 kHz; Fig.11 , 12 The unipolar hysteresis loop diagram and performance change diagram of the barium titanate-silver niobate ceramic prepared in Example 2 at different temperatures. DETAILED DESCRIPTION

[0018] The present invention is further described below by the following embodiments. It should be understood that the following embodiments are only used to illustrate the present invention, but not to limit the present invention.

[0019] First, the present invention provides a barium titanate-silver niobate relaxor ferroelectric ceramic with high polarization and high energy storage characteristics. The chemical composition of the barium titanate-silver niobate relaxor ferroelectric ceramic can be: (1-x)BaTiO3-xAgNbO3, 0.06≤x≤0.08.

[0020] The present invention selects a material with a polarization strength of up to 52 μC / cm 2 The high polarization antiferroelectric material silver niobate (AgNbO3) is dissolved in barium titanate. + , Ba 2+ and B-position Nb 5+ 、Ti 4+The difference in ionic radius and charge causes local heterogeneous structure and local electric field in ceramics, which refines ferroelectric domains into polar nanodomains, promoting the induction of relaxation behavior and reducing residual polarization. At the same time, the introduction of silver niobate compensates for the polarization loss of A site in BaTiO3 and the interruption of BO coupling by constructing new AO coupling, thereby maintaining the saturation polarization of barium titanate-based ceramics. At the same time, the induced lattice distortion refines the grains, and finally obtains ceramic materials with greatly improved breakdown field strength and energy storage density.

[0021] Compared with the introduction of other highly polarizable materials such as NaNbO3, the introduction of silver niobate in the present invention has a more significant effect on inducing the relaxation behavior of ceramics, and the prepared barium titanate-silver niobate has a higher polarization intensity under an external electric field. In addition, silver niobate is usually used as a matrix material in the field of ceramic energy storage. Although it has a high saturation polarization intensity, due to the inherent properties of silver niobate itself, the modified silver niobate-based ceramic material still presents a wide hysteresis loop, that is, low energy storage efficiency. The present invention introduces silver niobate as a relaxation end member into the barium titanate matrix, while increasing the energy storage density by increasing the polarization intensity, it also maintains high efficiency. The present invention introduces silver niobate, which is usually a matrix material, as a relaxation end member into the barium titanate matrix, and increases the polarization intensity by constructing a new Ag-O coupling therein, while increasing the energy storage density, it also maintains high efficiency.

[0022] That is, the present invention adjusts the relaxation behavior of ceramics by introducing different contents of AgNbO3 into barium titanate, thereby promoting the acquisition of ceramics with excellent energy storage performance and reliability. When the value of x is small, the ceramic exhibits a more obvious ferroelectricity, resulting in low energy storage performance; when the value of x is too large, it will lead to the appearance of a second phase, thereby greatly reducing the breakdown field strength, and the energy storage performance will also decrease accordingly.

[0023] In some embodiments, the breakdown field strength of the high energy storage characteristic barium titanate-silver niobate relaxor ferroelectric ceramic can be 554-665 kV / cm, and the recoverable energy density (energy storage density) can be 4.02-6.04 J / cm 3 , the energy storage efficiency can be 81.9~86.8%.

[0024] The following is an exemplary description of the preparation method of the high energy storage characteristic barium titanate-silver niobate relaxor ferroelectric ceramic provided by the present invention. The preparation method may include the following steps: (1) weighing barium carbonate powder, titanium dioxide powder, silver oxide powder, and niobium pentoxide powder as raw materials according to the element stoichiometric ratio in the chemical formula (1-x) BaTiO3-xAgNbO3, mixing the raw materials, calcining the raw materials under an oxygen atmosphere, and then finely grinding and sieving the raw materials to obtain ceramic powder; (2) adding a binder to the ceramic powder, granulating, screening and molding to obtain a ceramic green body; (3) The ceramic green body is molded and sintered in an oxygen atmosphere to obtain the barium titanate-silver niobate relaxor ferroelectric ceramic with high energy storage characteristics.

[0025] In some embodiments, in step (1), the purity of all raw material powders is at least 99%; the mixing method is planetary ball milling, and the mixing parameters include: the ball milling medium is anhydrous ethanol, the grinding balls are zirconia balls and zirconia columns, the ball milling speed is 200-240r / min, and the ball milling time is 4-6h; preferably, the particle size of the zirconia balls is 6mm, the size of the zirconia columns is 10mm in diameter × 10mm in height, the mass of the zirconia balls and the mass of the zirconia columns in the grinding balls each account for half, and the ball milling time is 4h.

[0026] In some embodiments, in step (1), the calcination temperature may be 1270-1330°C, the calcination time may be 2-3 hours, preferably 3 hours; the mesh size of the finely ground sieved sieve may be 40 meshes. By calcining in an oxygen atmosphere, the precipitation of Ag during the calcination process can be prevented; if the calcination temperature is too low, the raw materials will not react completely, and the pure phase (1-x)BaTiO3-xAgNbO3 powder cannot be synthesized; if the calcination temperature is too high, the powder properties will change, causing the performance to seriously deteriorate.

[0027] In some embodiments, in step (2), the binder may be a polyvinyl alcohol aqueous solution with a concentration of 6 to 7 wt.%, and the added amount may be 6 to 7 wt.% of the mass of the ceramic powder; the mesh size of the granulation screening may be 40 meshes.

[0028] In some embodiments, in step (3), the process of plastic removal can be: heating to 600-800°C at a rate of 2-4°C / min and keeping warm for 2-3h; preferably, heating to 800°C at a rate of 2°C / min and keeping warm for 2h.

[0029] In some embodiments, in step (3), the sintering process can be: heating to 1000°C at a heating rate of 2-4°C / min (preferably 3-4°C / min), and then heating to 1220-1280°C (preferably 1260-1280°C) at a heating rate of 2°C / min, and the holding time is 2-3h.

[0030] In addition, the present invention also provides an energy storage ceramic element. The high energy storage characteristic barium titanate-silver niobate relaxor ferroelectric ceramic is processed into a desired size, and the surface is coated with electrodes to obtain an energy storage ceramic element. That is, the energy storage ceramic device includes: the above-mentioned high energy storage characteristic barium titanate-silver niobate relaxor ferroelectric ceramic, and electrodes distributed on the surface of the high energy storage characteristic barium titanate-silver niobate relaxor ferroelectric ceramic.

[0031] The barium titanate-silver niobate relaxor ferroelectric ceramic with high energy storage characteristics obtained by the preparation method provided by the present invention can be applied to multilayer ceramic capacitors and pulse power devices (such as high-power pulse capacitors).

[0032] The following further examples are given to illustrate the present invention in detail. It should also be understood that the following examples are only used to further illustrate the present invention and cannot be construed as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above content of the present invention all belong to the scope of protection of the present invention. The specific process parameters of the following examples are also only examples within a suitable range, that is, those skilled in the art can make selections within a suitable range through the description of this article, and are not limited to the specific values ​​​​exemplified below. If not specifically stated, the technical means used in the embodiments are conventional means well known to those skilled in the art.

[0033] Example 1

[0034] The preparation method of the barium titanate-silver niobate relaxor ferroelectric ceramic (x=0.06) with high energy storage characteristics provided in this embodiment comprises the following steps: (1) Weigh raw materials according to the chemical element stoichiometric ratio of the molecular formula 0.94BaTiO3-0.06AgNbO3, including: barium carbonate powder (purity 99.95%), titanium dioxide powder (purity 99.9%), silver oxide powder (purity 99.7%), and niobium pentoxide powder (purity 99.99%), with a weighing accuracy of 0.001 g; mix the weighed raw materials and put them into a nylon tank, add anhydrous ethanol no higher than 2 / 3 of the tank height, and add oxygen with a particle size of 6 mm. Zirconium oxide balls and zirconium oxide columns with a diameter of 10 mm and a height of 10 mm are used as grinding balls, each accounting for half of the mass. The nylon jar is placed on a planetary ball mill and ball-milled for 4 hours at a speed of 200 r / min, then poured into a glass plate, dried in an oven at 80°C, and then sieved with a 40-mesh screen to obtain a fully mixed powder; the above powder is pressed into a cylinder with a size of 65 mm in diameter and 20 mm in height on a press, calcined at 1290°C for 3 hours in an oxygen atmosphere, and then crushed through a 40-mesh screen to obtain a ceramic powder; (2) adding a 6 wt % polyvinyl alcohol aqueous solution as a binder to the ceramic powder, the mass of the added polyvinyl alcohol aqueous solution being 7% of the mass of the ceramic powder, and then fully grinding and granulating, sieving, and molding to obtain a ceramic green body; wherein the mesh size of the sieve used is 40 meshes, and the ceramic green body is a small cylinder with a diameter of 13 mm and a height of 1 mm; (3) In an oxygen atmosphere, the ceramic green body is heated to 800°C at a rate of 2°C / min and kept at this temperature for 2 hours to obtain a ceramic green body after molding; in an oxygen atmosphere, the ceramic green body after molding is heated to 1000°C at a rate of 4°C / min, and then heated to 1260°C at a rate of 2°C / min and kept at this temperature for 3 hours. After naturally cooling to room temperature, the sintered ceramic block is taken out to obtain the barium titanate-silver niobate relaxor ferroelectric ceramic with high energy storage characteristics.

[0035] Example 2

[0036] The preparation method of the high energy storage characteristic barium titanate-silver niobate relaxor ferroelectric ceramic provided in this embodiment refers to that in Example 1, with the main differences being: (1) x=0.08; and (2) the calcination temperature is 1280°C.

[0037] Comparative Example 1

[0038] The preparation method of the barium titanate-silver niobate ceramic provided in this comparative example 1 refers to that in Example 1, with the main differences being: (1) x=0.02.

[0039] Comparative Example 2

[0040] The preparation method of the barium titanate-silver niobate ceramic provided in this comparative example 2 refers to that of Example 1, with the main differences being: (1) x=0.04.

[0041] Comparative Example 3

[0042] The preparation method of the barium titanate-silver niobate ceramic provided in this comparative example 3 refers to that in Example 1, with the main differences being: (1) x=0.10; and (2) the calcination temperature is 1280°C.

[0043] Figure 1 The X-ray diffraction images of the barium titanate-silver niobate ceramic materials prepared in Examples 1 and 2 and Comparative Examples 1 to 3 are shown in FIG. As can be seen from the figure, after AgNbO3 is dissolved into BaTiO3, all barium titanate-silver niobate ceramics present a perovskite structure, proving the successful preparation of barium titanate-silver niobate ceramics.

[0044] Field emission scanning electron microscopy was used to observe the surface morphology of the ceramic blocks. Figure 2 , 3 The surface morphology of the high energy storage property barium titanate-silver niobate relaxor ferroelectric ceramics prepared in Examples 1 and 2. It can be seen from the figure that the surface grains of the barium titanate-silver niobate relaxor ferroelectric ceramics prepared in Examples 1 and 2 are well-developed, small and dense.

[0045] The ceramic was thinned on both sides to obtain the middle part, gold electrodes were sputtered, and the energy storage performance was tested. Figure 4 , 5The unipolar hysteresis loop diagram of the high energy storage characteristic barium titanate-silver niobate relaxor ferroelectric ceramic prepared in Examples 1 and 2. It can be seen from the figure that the hysteresis loops of Examples 1 and 2 are slender while maintaining a relatively high saturation polarization intensity, thereby obtaining high energy storage performance.

[0046] Figure 6 , 7 8 is a unipolar hysteresis loop diagram of the barium titanate-silver niobate ferroelectric ceramic prepared in comparative examples 1-3. It can be seen from the figure that the ferroelectricity of the barium titanate-silver niobate ceramic prepared in comparative examples 1-2 is still strong, and the breakdown field strength of the barium titanate-silver niobate ceramic prepared in comparative example 1 is only 324 kV / cm, and the energy storage density is only 1.95 J / cm 3 The energy storage efficiency is 70.7%. The breakdown field strength of the barium titanate-silver niobate ceramic prepared in Comparative Example 2 is only 398 kV / cm and the energy storage density is 2.57 J / cm 3 The energy storage efficiency is 77.7%, and the breakdown field strength of the barium titanate-silver niobate ceramic prepared in comparative example 3 is only 417 kV / cm, and the energy storage density is 3.20 J / cm 3 , the energy storage efficiency is 83.3%.

[0047] Fig. 9 The performance comparison diagram of the barium titanate-silver niobate ceramics with different components prepared in Examples 1 and 2 and Comparative Examples 1-3 is shown in the figure. It can be seen from the figure that the solid solution of silver niobate will improve the energy storage density and efficiency of the barium titanate-based ceramics, but when the amount of silver niobate introduced is too high, the energy storage performance will decrease. Therefore, the optimal energy storage performance can be obtained by reasonably controlling the solid solution amount of silver niobate.

[0048] Fig.10 The dielectric temperature spectra of the barium titanate-silver niobate ceramics with different components prepared in Examples 1 and 2 and Comparative Examples 1-3 at a frequency of 1 kHz. It can be seen from the figure that the breakdown field strength of the barium titanate-silver niobate ceramics prepared in Example 1 is 554 kV / cm and the energy storage density is 4.02 J / cm 3 , the energy storage efficiency is 81.9%, the breakdown field strength of the barium titanate-silver niobate ceramic prepared in Example 2 is 665 kV / cm, and the energy storage density is 6.04 J / cm 3 , the energy storage efficiency is 86.8%, the solid solution of AgNbO3 reduces the Curie temperature of the ceramic, and the dielectric peak broadens and the frequency dispersion becomes more obvious, indicating that the ceramic transforms from a ferroelectric to a relaxor ferroelectric.

[0049] Fig.11 , 12 The unipolar hysteresis loop diagram and performance change diagram of the barium titanate-silver niobate ceramic at different temperatures prepared in Example 2. It can be seen from the figure that the performance fluctuation of the ceramic prepared in Example 2 is small in the temperature range of -40 to 120°C, indicating its excellent temperature stability.

[0050] Table 1 below is a comparison of the performance parameters of the high energy storage characteristic barium titanate-silver niobate relaxor ferroelectric ceramics prepared by the present invention: x <![CDATA[Recyclable energy storage density (J / cm 3 )]]> Energy storage efficiency / % Breakdown electric field (kV / cm) Example 1 0.06 4.02 81.9% 554 Example 2 0.08 6.04 86.8% 665 Comparative Example 1 0.02 1.95 70.7% 324 Comparative Example 2 0.04 2.57 77.7% 398 Comparative Example 3 0.10 3.20 83.3% 417

[0051] It can be seen from Table 1 that the solid solution of AgNbO3 continuously enhances the energy storage performance of the ceramic. The breakdown field strength of Examples 1 and 2 is relatively high, and the energy storage performance is excellent.

[0052] In summary, in the present disclosure, the inventors studied the preparation of ceramics with different AgNbO3 solid solution contents (x = 0.02, 0.04, 0.06, 0.08, 0.10) and their effects on performance based on the problem that the saturation polarization of ceramics decreases significantly during the process of inducing relaxation behavior. The solid solution of AgNbO3 effectively induces the relaxation behavior of BaTiO3-based ceramics, but the saturation polarization strength of each component ceramic is basically maintained at the same level (~34μC / cm 2 ). Combined with the improvement of breakdown field strength, the energy storage performance of ceramics continues to increase, but too much AgNbO3 solid solution will lead to a decrease in breakdown field strength and energy storage performance. Only when the amount of AgNbO3 is appropriate can high energy storage characteristics be achieved.

[0053] Although the content of the present invention has been described in detail through the above preferred embodiments, it should be appreciated that the above description should not be considered as a limitation of the present invention. After reading the above content, it will be apparent to those skilled in the art that various modifications and substitutions of the present invention will occur. Therefore, the protection scope of the present invention should be limited by the appended claims.

Claims

1. A barium titanate-silver niobate relaxor ferroelectric ceramic with high energy storage characteristics, characterized in that: The chemical composition of the barium titanate-silver niobate relaxor ferroelectric ceramic is: (1-x)BaTiO3-xAgNbO3; wherein 0.06≤x≤0.

08.

2. The barium titanate-silver niobate relaxor ferroelectric ceramic with high energy storage characteristics according to claim 1, characterized in that: The high energy storage characteristic barium titanate-silver niobate relaxor ferroelectric ceramic has a breakdown field strength of 554-665 kV / cm and a recoverable energy density of 4.02-6.04 J / cm 3 , the energy storage efficiency is 81.9~86.8%.

3. A method for preparing the barium titanate-silver niobate relaxor ferroelectric ceramic with high energy storage characteristics according to claim 1 or 2, characterized in that: The preparation method comprises the following steps: (1) weighing barium carbonate powder, titanium dioxide powder, silver oxide powder, and niobium pentoxide powder as raw materials according to the element stoichiometric ratio in the chemical formula (1-x) BaTiO3-xAgNbO3, mixing the raw materials, calcining the raw materials under an oxygen atmosphere, and then finely grinding and sieving the raw materials to obtain ceramic powder; (2) adding a binder to the ceramic powder, granulating, screening and molding to obtain a ceramic green body; (3) Arranging and sintering the ceramic green body in an oxygen atmosphere to obtain the barium titanate-silver niobate relaxor ferroelectric ceramic with high energy storage characteristics.

4. The preparation method according to claim 3, characterized in that: In step (1), the purity of the raw material powder is at least 99%; The mixing method is planetary ball milling, and the mixing parameters include: the ball milling medium is anhydrous ethanol, the grinding balls are zirconia balls and zirconia columns, the ball milling speed is 200-240r / min, and the ball milling time is 4-6h; preferably, the particle size of the zirconia balls is 6mm, the size of the zirconia columns is 10mm in diameter×10mm in height, the mass of the zirconia balls and zirconia columns in the grinding balls each accounts for half, and the ball milling time is 4h.

5. The preparation method according to claim 3 or 4, characterized in that: In step (1), the calcination temperature is 1270-1330° C., and the calcination time is 2-3 hours, preferably 3 hours; The mesh number of the fine grinding and sieving is 40 meshes.

6. The preparation method according to any one of claims 3 to 5, characterized in that: In step (2), the binder is a polyvinyl alcohol aqueous solution with a concentration of 6 to 7 wt.%, and the added amount is 6 to 7 wt.% of the mass of the ceramic powder; the mesh size of the granulation screening is 40 meshes.

7. The preparation method according to any one of claims 3 to 6, characterized in that: In step (3), the process of plastic removal is: heating to 600-800°C at a rate of 2-4°C / min and keeping warm for 2-3h; preferably, heating to 800°C at a rate of 2°C / min and keeping warm for 2h.

8. The preparation method according to any one of claims 3 to 7, characterized in that: In step (3), the sintering process is: heating to 1000°C at a heating rate of 2-4°C / min, then heating to 1220-1280°C at a heating rate of 2°C / min, and keeping the temperature for 2-3h.

9. An energy storage ceramic element, characterized in that: The energy storage ceramic device comprises: the barium titanate-silver niobate relaxor ferroelectric ceramic with high energy storage characteristics as claimed in claim 1 or 2, and electrodes distributed on the surface of the barium titanate-silver niobate relaxor ferroelectric ceramic with high energy storage characteristics.

10. Use of the barium titanate-silver niobate relaxor ferroelectric ceramic with high energy storage characteristics as claimed in claim 1 or 2 in multilayer ceramic capacitors and pulse power devices.

Citation Information

Patent Citations

  • Antiferroelectric ceramic and preparation method thereof

    CN113024248A

  • Silver niobate-based antiferroelectric energy storage ceramic with high energy storage characteristic, and low-temperature sintering method thereof

    CN113683419A

  • Silver niobate-based relaxation type ternary solid solution ceramic material with high energy storage characteristic and preparation method of silver niobate-based relaxation type ternary solid solution ceramic material

    CN117285354A

  • Porcelain composition

    JP1992240150A